Producción, purificación y evaluación de los atributos de calidad de la enzima m - mlv retrotranscriptasa (rt) obtenida in house mediante un sistema recombinante en e. coli bl21 (de3) (2024)
The PCR technique has revolutionized molecular research, facilitating accurate and reliable diagnostics of diseases that represent a public health problem. Its variant, RT-PCR, allows the amplification of millions of copies starting from RNA for its conversion to DNA, being crucial in diseases such as COVID-19, HIV, dengue, and Zika. However, the dependence on imported reagents, especially one of the most critical components, the M-MLV RT enzyme; makes its implementation more expensive, especially in urgent clinical scenarios, such as the recent pandemic. This enzyme, key for reverse transcription, is mostly obtained from viral sources, with high costs and prolonged import times, limiting its clinical availability in Colombia. Given the above, this project addresses the local production of the reverse transcriptase enzyme M-MLV RT (later. (See Annex 1b - Figure 13). Regarding Lot II, according to the results reported in Table 14, the Cq values remained similar within 4 weeks post-production of the enzyme, showing higher amplification cycles in week 8. However, this value presents a considerable degree of accuracy with respect to the commercial standard, so it could be inferred that this variation presumably corresponds to some alteration in the integrity of the starting genetic material, such as a change in the concentration of viral RNA. Thus, if the amount of genetic material in the sample is lower, amplification will proceed more slowly and more cycles will be needed for the amplification signal to exceed the threshold. Likewise, it is worth noting that lower Cq values are evident in the replicates stored at -20°C in contrast to the values resulting from refrigeration at 4°C. Qualitatively, Figure 10 shows the amplification profiles with a considerable level of similarity. Likewise, it should be noted that despite presenting variations in concentration or a certain degree of remaining impurities after the purification process, it does not seem to directly affect the biological activity of the Reverse Transcriptase; since the results suggest very similar amplification profiles with respect to the recombinant enzymes, these being comparable to the functionality of the commercial enzyme without significant differences between storage at -20°C and 4°C.